Health Needs Assessment for Problem Prioritization in a Primary Healthcare Facility - Shifa Umar, Abdul Mannan Khan Minhas, Kashaf Naeem Malik, Haaris Ali Arshad, Muhammad Faisal Aslam,Muhammad Saad Shahid (Journal of Rawalpindi Medical College, 2014)
Background: To determine health needs and potential factors affecting risk behaviors for prioritization of health problems. Methods: In this cross sectional study data was collected through two structured questionnaires using convenience sampling. Questions were asked about the patients and their families. They were evaluated for prevalence of acute and chronic diseases and various risk factors, including hand-washing habits, drinking water, and consumption of staple diet. Results: Each household had an average 10 family members each. The frequency of individuals employed was 60% and self-employed were 25%. The average monthly income was 7000-15000 rupees .Majority (86.7%) individuals owned kacha houses.Water filtration system or boiled water was not a practice in majority (78%).Meat consumption was once a month or less than that in 68% . Conclusion: There is lack of basic hygienic habits among the population of Nurpur Shahan, which is responsible for prevalence of acute infections. The study enables us to identify the actions required to address these health problems that will, in turn, promote wellbeing of the community.